2008
DOI: 10.1152/ajpendo.00780.2007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of continuous positive airway pressure therapy on hypothalamic-pituitary-adrenal axis function and 24-h blood pressure profile in obese men with obstructive sleep apnea syndrome

Abstract: Sympathetic nervous system and hypothalamic-pituitary-adrenal (HPA) axis activation may be the mechanism of this relationship. The aim of this study was to evaluate HPA axis and ambulatory blood pressure monitoring in obese men with and without OSAS and to determine whether nasal continuous positive airway pressure therapy (nCPAP) influenced responses. Twenty-four-hour ambulatory blood pressure monitoring and overnight cortisol suppression test with 0.25 mg of dexamethasone were performed in 16 obese men with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
50
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 40 publications
(46 reference statements)
4
50
0
4
Order By: Relevance
“…In agreement with our results, Carneiro, et al showed that a blunted response of cortisol suppression after 0.25 mg DST in obese men with OSAS compared with obese male controls, which were recovered by CPAP therapy [21]. The previous reports including Carneiro's study were that the effect of CPAP therapy for the HPA axis in OSAS patients was examined three months after CPAP therapy [11,[21][22][23].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement with our results, Carneiro, et al showed that a blunted response of cortisol suppression after 0.25 mg DST in obese men with OSAS compared with obese male controls, which were recovered by CPAP therapy [21]. The previous reports including Carneiro's study were that the effect of CPAP therapy for the HPA axis in OSAS patients was examined three months after CPAP therapy [11,[21][22][23].…”
Section: Discussionsupporting
confidence: 92%
“…The previous reports including Carneiro's study were that the effect of CPAP therapy for the HPA axis in OSAS patients was examined three months after CPAP therapy [11,[21][22][23]. On the other hand we performed 0.5 mg DST for them within a few but not with AHI (p=0.784), BMI (p=0.984), waist circumference (p=0.967), HbA1c (p=0.261), fasting plasma glucose (p=0.420) or HOMA-IR (p=0.500).…”
Section: Discussionmentioning
confidence: 99%
“…Cortisol is another hormone synthesized in response to conditions such as those in OSA patients [57]. However, serum cortisol concentrations in OSA patients were not statistically different from those in control group.…”
Section: Discussionmentioning
confidence: 89%
“…Given the above limitations, it is no surprise that studies on the effects of continuous positive airway pressure (CPAP) treatment on HPA axis activity have yielded inconsistent findings [8,10,11,[13][14][15][16][17]. In addition, most of the CPAP studies have been confounded by methodological limitations such as lack of a control group at baseline, or a placebo control group, as well as a small sample size.…”
Section: Introductionmentioning
confidence: 99%